Sunrise on the Reaping - Collins, Suzanne (New York : Scholastic Press, 2025)
Sunrise on the Reaping revisits the world of Panem twenty-four years before the events of The Hunger Games, starting on the morning of the reaping of the Fiftieth Hunger Games, also known as the Second Quarter Quell.
Keywords: Contests -- Juvenile fiction; Dystopias -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Young adult fiction; Science fiction; Dystopian fiction